Devices in Vascular Access: Is Technology Overtaking Evidence?. Issue 2 (March 2014) - Inston, Nicholas G.; Jones, Robert
Abstract: Advances in device technology have led to a rapid expansion in the number of available devices, which can be used for the formation and maintenance of vascular access. Whilst this may appear to be improving outcomes, there is little evidence to support the use of these devices over currently available methods. Most of the evidence that is available is from small studies with an absence of robust well-designed trials. The examples of "quick-stick" grafts and drug-eluting balloons serve to illustrate this. Whilst there is an enthusiasm for the potential benefits of novel devices there is also a risk - both economically and clinically - to adopting new practices without appropriate and valid comparisons to be made.